2011
DOI: 10.1080/15504263.2011.620429
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Trauma-Informed Care Readiness in Behavioral Health: An Organizational Case Study

Abstract: Objective: In this organizational case study the authors pilot a new protocol for evaluating and developing trauma-informed care in behavioral health settings. Methods: A mixed methods design was used to collect data with three instruments: the Adverse Childhood Experiences, the Consumer Perceptions of Care, and the Community Readiness Model key informant interview. Adults (N = 138) in a behavioral health residential treatment program provided a consumer perspective on trauma and integrated services. Providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…These insights further strengthened health professionals’ recognition of the benefits to implementing a trauma-informed approach. This is consistent with previous research that shows health professionals are more supportive of providing a safer environment for consumers when they are aware of the effects of trauma and violence (Farro et al, 2011; Hopper et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…These insights further strengthened health professionals’ recognition of the benefits to implementing a trauma-informed approach. This is consistent with previous research that shows health professionals are more supportive of providing a safer environment for consumers when they are aware of the effects of trauma and violence (Farro et al, 2011; Hopper et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Findings from this study suggest that the educational sessions helped staff understand the significance of past trauma and allowed them to view current behaviour or emotional responses by young inpatient service users with greater understanding. This finding is consistent with the broader literature which has shown that TIP education can positively impact staff knowledge, attitudes, language and practices (Akin et al., 2021; Baker et al., 2018; Connell et al., 2019; Farro et al., 2011; Lang et al., 2016; Palfrey et al., 2019). Experts suggest that education should include the principles of TIP, integrated into practice (Bowen & Murshid, 2016; Guha et al., 2022; Shier and Turpin, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…In a study on the adoption of cognitive therapy among clinicians, workload (excessive paperwork) and productivity requirements were found to be the most predictive barriers to implementation (Stirman et al, 2013). Farro, Clark, and Hopkins-Eyles (2011) determined that perception of available resources created a lower sense of readiness despite an understanding of and ability to deliver trauma-informed services.…”
Section: Organizational Strainmentioning
confidence: 99%
“…This comprehensive assessment involves case file review, review of agency records, interviews, and focus groups. According to Farro et al (2011), "This instrument provides a gold standard assessment that has defined trauma-informed care and provided one of the first in-depth assessments of trauma-informed practices" (p. 230).…”
Section: Current Tic Assessment Instrumentsmentioning
confidence: 99%